Management of Fetal Mummification in a Crossbred Heifer with Dinoprost Tromethamine and Estradiol Benzoate - Gupta, Chhavi; Arunachalam, Ramprabhu R.; Subramanian, Ganesh K.; Edwin, Soosaimarian C. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Fetal mummification is an accident during the gestation period, and its incidence is 0.13-1.8% in cows (Kumar and Saxena, 2018), which is characterized by resorption of fetal fluids and fetus surrounded by chocolate-colored material (Kumar et al., 2017)